Immunofluorescence Study of Wild Rabies Virus and Antibody - Schneider, Morris D. (1966)
A concentrate of wild rabies antibody was prepared from hyperimmune serums of three dogs refractory to wild rabies. The animals resisted repeated intramuscular injections of large doses of wild rabies virus in emulsions of whole brain, in emulsions of submaxillary salivary glands, and in emulsified mixtures of brain and submaxillary glands taken from naturally rabid dogs. The antibody was conjugated with fluorochrome and then absorbed by a procedure that gave “cell-free” working solutions of fluorescent antibody. The procedure entailed parallel absorption steps with minced pathological canine submaxillary glands from (1) naturally rabid dogs (these glands contained specific, undegraded, natural antigens of live wild rabies virus plus nonspecific substances and antigens) and (2) nonrabid dogs from a rabies endemic region (these glands contained nonspecific substances and antigens). Extracts from submaxillary glands of the three naturally rabid dogs and one nonrabid dog were stained with a cell-free solution of the fluorescent antibody. The glands of the rabid dogs contained fluorescent aggregates of intense green spherical and filamentous particles. When nonfluorescent canine hyperimmune serum was incubated with rabies-containing submaxillary extract, the rabies antigens were quenched. When nonfluorescent equine fixed virus antiserum was incubated with such extracts, the aggregates still retained bright fluorescence.